Non-radioactive chemical sequencing of biotin labelled DNA. - Richterich, P (1989)
Methods for the nonradioactive chemical sequencing of DNA are described. A biotin marker molecule, attached chemically to an oligonucleotide primer or enzymatically in an endfilling reaction of restriction enzyme sites, is stable during the base-specific chemical modification and strand scission reactions. Following fragment separation by direct blotting electrophoresis, the membrane bound sequence pattern can be visualized by a streptavidin-bridged enzymatic color reaction. The biotin labeling is also applicable for DNA sequencing by random degradation of phosphothioates, thus showing to be a universal label for nonradioactive DNA sequencing.